COMMUNICATION AND INFORMATION MANAGEMENT AND STUDENTS’ CRISES RESOLUTION IN PUBLIC UNIVERSITIES IN NIGERIA - Oyetakin Akinrotimi Iyiomo (European Scientific Journal, ESJ, 2014)
The 21st century argument for the promotion and management of Information and Communication in the delivery of education in developed and some developing economies gave birth to a planned form of using technology to bridge the gap between the university management and staff and students. Information and communication (IC) for emergency management functions best when its design follows from a solid understanding of the sociotechnical systems that it is meant to support. This study examined the impact of Information and Communication in the management of crisis and to determine the existing relationship between staff/student needs and conflicts in the public universities in South West Nigeria. The increasing number of crises made communication a more demanding job for managers. Organizations face small crises every day, such as charges of denial of staff and students needs in Nigeria universities. This study adopt the descriptive research design of survey type. Nigeria is made up of six geo-political zones namely: North-West, North-East, North-Central, South-South, South- East, and South-West. Thus, a purposive simple random sampling method was adopted and the South-West geo-political zone was selected out of which three (3) Federal universities and three (3) State universities were randomly selected. A stratified sampling technique was also used to select 2,400 consisting of 300 students and 100 academic and non-academic staff from each university. The instrument used was a self constructed questionnaire titled, Information Communication Technology and Crises Resolution Questionnaire (ICTCRQ). Before administration, the questionnaire was validated with reliability coefficient of r = 0.87. Data were analyzed through descriptive and inferential statistics tools to test the research hypotheses for the study. The result reveals that there is a significant difference between the level of information communication management and crisis between the Federal and State Universities. (df =(5, 397), F-cal = .297 > F-tab= .157 ; P < .05). The study also revealed that is a significant relationship between information communication management and student crisis resolution in Universities (r=0.66, P<0.05). On the basis of the findings, it is therefore recommended that Management of the university system has a task of playing the unique leadership role to identify early conflict signals, prevent emergence of conflict and control or resolve an existing ones with the effective uses of modern ICT gadgets to ensure effective and efficient attainment of the university objectives.